O papel do gestor de competências do currículo escolar da educaçao básica na inspetorias Sao Joao Bosco - Sobrinho, Gervasio Bassini (2011)
BASSINI SOBRINHO, Gervásio. The role of the manager of curricular competence of the basic education in schools of Province of St. John Bosco. 2012. 150 p. Thesis submitted for the degree of Master of Science in Education, Educational Management mention - Quito: Universidad Politécnica Salesiana. This dissertation is the result of a survey conducted in the schools of the St. John Bosco Province (ISJB). His concern is for the role of the manager of curricular competence of the basic education in schools of ISJB. Its overall goal is to develop a proposal of continued education and upgrade for managers of curricular competence and educators in the schools of basic education of the ISJB. This will allow schools to respond with quality and significance to new needs of formation and learning of student. For this, within the specific objectives, this dissertation attempts to analyze the strengths and vulnerabilities that arise in addressing curricular by competence, explain in a theoretical way the relevance of the implementation of the curriculum by competence to reframe the experience of formation and learning, develop a proposal of formation and constant upgrading for managers and educators. As planned, with data collected in the survey, this work provides elements for managers in order to help them understand their role, to help them to interfere in the practice of educators and to create reliable parameters for the management of curricular competence. Established the benchmarks of the research, the starting point is the development of strategic diagnosis by means of which are identified in the experience of curricular approach by competencies, strengths and vulnerabilities to understand the attitude of resistance and incrustation in tradition. The next step is an analysis of the curriculum of competence and meaningfulness of the Salesian Educative Process, with the relevance of the implementation of the curriculum by competencies. This dissertation is structured in four chapters: referential of the research, strategic diagnosis, analysis of the curriculum by competence and meaningfulness of the Educative Salesian Process, proposal of continued formation and upgrading for managers and educators, ending with conclusions and recommendations.